2018
DOI: 10.1002/cld.682
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐arterial locoregional therapy in the management of hepatocellular carcinoma

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/11-1-reading-ramanathan.html a video presentation of this article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…(TACE) is a palliative treatment for patients without a curative treatment option for intermediate-stage HCC (Barcelona Clinic Liver Cancer stage B) (3,4). TACE is an endovascular technique that delivers the combination of an anticancer agent and the iodized oil to local lesions of the tumor (5). Adverse events associated with gastrointestinal (GI) symptoms include nausea, vomiting, abdominal bloating, loss of appetite, constipation, and other symptoms (6).…”
Section: Introductionmentioning
confidence: 99%
“…(TACE) is a palliative treatment for patients without a curative treatment option for intermediate-stage HCC (Barcelona Clinic Liver Cancer stage B) (3,4). TACE is an endovascular technique that delivers the combination of an anticancer agent and the iodized oil to local lesions of the tumor (5). Adverse events associated with gastrointestinal (GI) symptoms include nausea, vomiting, abdominal bloating, loss of appetite, constipation, and other symptoms (6).…”
Section: Introductionmentioning
confidence: 99%
“…5 Conventional transarterial chemoembolization is limited by side effects but this has been improved through the use of drug-eluting beads (DEB-TACE). 6 Main portal vein thrombosis is often seen as a contraindication to chemoembolization due to the increased risk of hepatic insufficiency, but some studies have shown a potential benefit. 7 Transarterial radioembolization (TARE) is a targeted therapeutic approach which facilitates direct delivery of yttrium-90 loaded microspheres to the tumor and may be the preferred treatment in the case of portal vein thrombosis.…”
Section: Introductionmentioning
confidence: 99%